What differences can performance ratings make? Difference-in-difference estimates of impact on local government responsiveness in the Philippines - Joseph J. Capuno; Maria Melody S. Garcia (University of the Philippines, School of Economics (UPSE), 2009)
In many countries that have decentralized, improving the accountability of local officials is increasingly emphasized to make them more responsive to their constituents' needs. This paper provides evidence that the public announcement of performance ratings can induce local governments to become responsive. The evidence is based on application of a difference-in-difference method on a unique household-level dataset collected during the three-year pilot test of a rating system in 12 municipalities and cities in the Philippines. The results are consistent with the predictions of political agency models of incumbent behavior. Some policy guidelines on the design and implementation performance benchmarks are made.
Keywords: H11; H30; H77; C93; 330; Local governments; political agency; performance ratings; decentralization; Kommunalverwaltung; Good Governance; Dezentralisierung; Performance-Messung; Schätzung; Philippinen